An investigation of the relationship between sukuk and the performance of banks of Pakistan - Sitara Bibi; Fatima Mazhar (State Institute of Islamic Studies (IAIN) Salatiga, 2019)
Using panel data analysis, this study investigates the relationship among Islamic bonds (Sukuk) and the performance of IB’s of Pakistan for the period of 2008-2017. The study has used two stages approach. At the first stage, the profitability and liquidity of banks have been measured by calculating financial ratios. These ratios were than further used in regression analysis to examine whether a relationship exists between Sukuk and the bank’s profitability and liquidity. Our study found a significant positive relationship among Sukuk and the liquidity of IB’s. While, the results show significant but negative relationship between Sukuk and profitability of IB’s. Based on the findings of the study, we concluded that Sukuk has an important role in enhancing the liquidity of IB’s but it has adverse impact on the profitability of IB’s of Pakistan. Thus, the emergence of Sukuk market may pose threats to the profitability of the IB’s of Pakistan.